1905 N.H. Laws 515, An Act to Prohibit the Use of Swivel and Punt Guns, ch. 98, § 1. - (:unkn) unknown (General Publisher, 1905)
IF any person shall, at any time, within this state, hunt, pursue, shoot at, or kill any game bird, as defined by section 34 of chapter 79 of the laws of 1901, with any punt gun swivel gun, or other gun not fired from the shoulder, or of larger bore than ten gauge, he shall be fined not more than ten dollars for each offense and shall forfeit all guns and implements with which the offense was committed.
--
Keywords: HUNTING REGULATION